2000
DOI: 10.1046/j.1523-1755.2000.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting patient outcome from acute renal failure comparing three general severity of illness scoring systems

Abstract: The APACHE II model was a slightly better calibrated predictor of group outcome in ARF patients, as compared with the SAPS II and MPM24 II outcome prediction models. The MPM24 II model showed the best discrimination capacity, in comparison with both APACHE II and SAPS II models, but it constantly and significantly overestimated mean predicted mortality in ARF patients. None of the models provided sufficient confidence for the prediction of outcome in individual patients. A high degree of caution must be exerte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 41 publications
3
43
1
Order By: Relevance
“…[12] In a comparative study of the three different organ failure scoring systems, none could predict outcome in individual patients. [13] Herbert et al showed a strong association between the number of organ system failures and 30-day mortality in a prospective study of sepsis patients. [14] In another study on multiorgan dysfunction syndrome, the continuous variables of multiple organ dysfunction score were converted to discrete cutoff points to define the presence or absence of organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…[12] In a comparative study of the three different organ failure scoring systems, none could predict outcome in individual patients. [13] Herbert et al showed a strong association between the number of organ system failures and 30-day mortality in a prospective study of sepsis patients. [14] In another study on multiorgan dysfunction syndrome, the continuous variables of multiple organ dysfunction score were converted to discrete cutoff points to define the presence or absence of organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic and clinical data were taken from the clinical and administrative database of the ward, including the Acute Physiology and Chronic Health Evaluation (APACHE) score in version II (31) at RRT start (32), and the Model for End-Stage Liver Disease (MELD) score (33). MELD is a prospectively developed and validated liver disease severity scoring system that uses a patient's laboratory values for serum bilirubin, serum creatinine, and the international normalized ratio for prothrombin time.…”
Section: Data Collectionmentioning
confidence: 99%
“…Generic severity-of-illness scoring systems (e.g., Acute Physiology and Chronic Health Evaluation-II [APACHE II], Simplified Acute Physiology Score [SAPS], and Logistic Organ Dysfunction Score [LODS]) have not discriminated well in most published studies of ARF (15)(16)(17)(18). Although several authors have proposed disease-specific indices, most have been derived at single centers (19 -22), and few have been validated outside of their original institution (23)(24).…”
mentioning
confidence: 99%